Benefits of Traditional Fortification Games in the Gross Motor Aspects of Early Childhood - Citra Aldini; Heri Yusuf Muslihin; Risbon Sianturi (CV. Rayyan Dwi Bharata, 2023)
The development of increasingly advanced technology has brought social changes that affect the existence of traditional games. Nonetheless, traditional games have important value in developing various aspects of children's motor skills. One of the traditional games that can develop children's gross motor skills is the game of fort. Fortress games attract children's attention and have benefits that are not widely known in improving children's gross motor skills. The purpose of this study is to better understand the benefits of traditional games in depth, especially in the gross motor aspects of children. This study uses a descriptive qualitative design, with data collection techniques through interviews, observation, and documentation. The results of this study will reveal the benefits contained in traditional fortification games in developing children's gross motor skills.